2015
DOI: 10.1126/scitranslmed.aaa7322
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated pathology in Duchenne muscular dystrophy

Abstract: Immunological and inflammatory processes downstream of dystrophin deficiency as well as metabolic abnormalities, defective autophagy, and loss of regenerative capacity all contribute to muscle pathology in Duchenne muscular dystrophy (DMD). These downstream cascades offer potential avenues for pharmacological intervention. Modulating the inflammatory response and inducing immunological tolerance to de novo dystrophin expression will be critical to the success of dystrophin-replacement therapies. This Review fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
249
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(269 citation statements)
references
References 108 publications
4
249
0
2
Order By: Relevance
“…Ablation or impaired recruitment of macrophages severely compromises muscle repair. Chronic muscle injury entails analogous shifts in innate immune system cell populations (6870). …”
Section: Skeletal Muscle Tregs: Facilitators Of Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation or impaired recruitment of macrophages severely compromises muscle repair. Chronic muscle injury entails analogous shifts in innate immune system cell populations (6870). …”
Section: Skeletal Muscle Tregs: Facilitators Of Repairmentioning
confidence: 99%
“…Though far less markedly, lymphocytes also accumulate in skeletal muscle after acute injury, as well as in the dystrophin-deficient muscles of mice harboring the mdx mutation or humans with Duchenne’s muscular dystrophy (DMD) (63, 68, 71). Their function has not been well studied, although both CD4 + and CD8 + T cells seem to promote the mdx pathology, and blocking their activities with immunosuppressants can ameliorate disease (72).…”
Section: Skeletal Muscle Tregs: Facilitators Of Repairmentioning
confidence: 99%
“…Presently, the only pharmacological therapy available to DMD patients is glucocorticoids , the administration of which has been associated with improved muscle strength and function and, crucially, a delay in the age at which patients become wheelchair‐bound . The beneficial effects of glucocorticoids are mostly due to their immunosuppressive effect , supporting the notion that the immune response plays an important role in the disease pathogenesis . Studies of the muscle infiltrate in DMD patients' biopsies have shown that it is composed of mostly macrophages and T cells and that corticosteroid treatment reduces their number .…”
Section: Introductionmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disorder caused by a mutation in the dystrophin gene . The absence of functional dystrophin protein is responsible for membrane fragility and repeated myocytic damage which lead to progressive muscle tissue destruction, associated with inflammation, ionic homeostasis dysregulation, energy metabolism alterations, exhaustion of regenerative capacities and, ultimately, replacement by fatty and fibrotic tissue. The nature and extent of how these mechanisms interact, however, are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%